Ein neues Antikoagulans zur Probengewinnung für Thrombozytenfunktionstests = A new anticoagulant for blood sampling tubes for platelet function tests - Wolf, Johanna; Sigl, Martin; Giannitsis, Evangelos; Ivandic, Boris (Laboratoriumsmedizin, 2010)
Background: The difficult pre-analytical conditions of platelet function diagnostics discourage its widespread use, e.g., to detect resistance to acetylsalicylic acid (ASA) and/or clopidogrel. Platelet activation during blood drawing and sample preparation cannot be prevented by citrate anticoagulation. Here, we tested a new blood sampling tube containing the anticoagulant benzylsulfonyl-D-argininyl-prolyl-4-amidinobenzylamide (Thrombovette ® , Probe & go, Osburg, Germany). Methods: A total of 46 emergency patients taking ASA and clopidogrel as well as 20 healthy volunteers were included in the study. Blood was drawn into Thrombovette ® and citrate S-Monovette ® tubes (Sarstedt AG&Co, Nümbrecht, Germany) and transported to the lab via the pneumatic tube system. Whole blood impedance aggregometry (model 560Ca, Chrono-Log, Havertown, PA, USA) was performed using collagen and ADP as platelet agonist (final concentrations 1 mg/L and 5 μM, respectively). Results: Reference ranges and cut-off values for the determination of drug resistance were obtained from the healthy cohort. Positive predictive values were 94.6% and 94.1% for inhibition of aggregation by ASA, and 68.0% and 53.3% for inhibition by clopidogrel using Thrombovette ® and citrate S-Monovette ® , respectively. Negative predictive values were 82.8% and 75.0% for ASA resistance and 87.8% and 83.3% for clopidogrel resistance using Thrombovette ® and citrate S-Monovette ® , respectively. Conclusions: Thrombovette ® is a promising new system for blood sampling and could improve the validity of platelet function diagnostics.
Gesehen am 21.03.2024